Jawabanmu

2014-02-20T16:13:26+07:00
* f(1)= a+b = 6 . . . . (persamaan 1) >> a= 6-b 
*f(3)= 3a+b = 10 . . . (persamaan 2)
dari persamaan 1 subtitusi ke persamaan 2 :
     3(6-b)+b = 10 >> 18-3b+b = 10 >> 18-10=2b >> b= 4
    a= 6-b >> a= 6-4=2

f(5)= 5a+b = 5(2)+4 = 14
1 3 1
2014-02-20T16:15:14+07:00
F(x)= ax +b
f(1) = 6   ⇒ a +b = 6
f(3) = 10 ⇒ 3a + b = 10 -
                 -2a = -4
                     a = 2
jadi, b = 6 - 2
       b = 4
sehingga. f (5) = 5a +b
                     = 5 (2) + 4
                       14